Pia Marchi Maggi - Agostini, Emanuela (Drammaturgia, 2021)
Born into an acting family, she was one of the most important leading actresses in the last 19th century. She performed in many excellent leading companies as such as those of Adelaide Ristori, Luigi Bellotti Bon and Andrea Maggi, her husband from 1880. Her repertory was distinguished by brilliant comedies and pochades, written mainly by French authors of the time, which brought out her comic talent.